2017
DOI: 10.7883/yoken.jjid.2015.454
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Typing of Enterobacteria Harboring LT and ST Enterotoxin Genes Isolated from Mexican Children

Abstract: SUMMARY: Enterotoxigenic Escherichia coli is the most common cause of diarrhea in children younger than 5 years in the developing world. We used 16S rRNA gene sequencing, the Biolog  system, and an Amplified Ribosomal DNA Restriction Analysis (ARDRA) to identify 69 enterobacteria isolated from the feces of healthy children up to 12 years old and 54 enterobacteria isolated from stool samples obtained from children up to 5 years old with diarrhea from Morelia, Michoac áan, Mexico. In the diarrheic group, 18 iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In addition, it cannot be excluded that similar genes of virulence factors of other intestinal Enterobacteriaceae might be detected. As an example, a study performed on bacteria isolated from cases of diarrhoea in Children in Mexico showed the ST toxin gene of one strain identified as M. morganii being 100% identical to an ST toxin gene of E. coli [ 25 ]. The presence of genes encoding the LT toxin was previously reported in M. morganii obtained from stool samples of travelers with diarrhoea [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it cannot be excluded that similar genes of virulence factors of other intestinal Enterobacteriaceae might be detected. As an example, a study performed on bacteria isolated from cases of diarrhoea in Children in Mexico showed the ST toxin gene of one strain identified as M. morganii being 100% identical to an ST toxin gene of E. coli [ 25 ]. The presence of genes encoding the LT toxin was previously reported in M. morganii obtained from stool samples of travelers with diarrhoea [ 26 ].…”
Section: Introductionmentioning
confidence: 99%